Assessment of sea level rise and tidal flood vulnerability in the coastal region of Jepara, Central Java, Indonesia - Christiananda; Sawiji, Asri; Santoso, Eko Hadi (Journal of Marine Resources and Coastal Management, 2024)
The coastal region of Jepara, Central Java, is increasingly vulnerable to environmental hazards due to rising sea levels, land subsidence, and climatic variability. Recent public concerns regarding the potential submergence of parts of Jepara and the possible reappearance of the ancient Muria Strait underscore the need for a scientific assessment of regional coastal stability. This study aims to evaluate the impacts of sea level rise on the vulnerability of Jepara’s coastal areas to tidal inundation. Using secondary data from 2013 to 2024, the analysis includes trends in mean sea level (MSL), sea surface temperature (SST), and documented land subsidence in nearby coastal cities. The results indicate an average annual MSL increase of 4.23%, with projections reaching up to 3.83 meters by 2050 if current trends persist. SST also shows a consistent upward trend, contributing to thermal expansion and sea level rise. Tidal flood mapping reveals that rice fields and coastal settlements are the most affected land uses, with 1,960.66 hectares of agricultural land and 207.48 hectares of residential area exposed to periodic inundation. The compounded effects of sea level rise, SST increase, and subsidence suggest an urgent need for mitigation planning and adaptive infrastructure to reduce future flood risks.